PERAN MAQASHID SYARI'AH DALAM IJTIHAD - Herdiansyah Herdiansyah; Sri Hidayati (JURNAL HUKUM DAS SOLLEN, 2021)
ABSTRACT This paper is intended to examine the impact of Maqashid Shari'ah in Ijtihad. Maqashid Syari'ah was originally a sub-discussion in the study of Ushul Fiqh. But now Maqashid Shari'ah has its own study. Likewise with Ijtihad which is part of the discussion of Ushul Fiqh. Usul Fiqh experts usually put the discussion of Ijtihad at the end of each of their works. This does not indicate that the study of Ijtihad is not important compared to other studies. This is because ijtihad is the conclusion of all the discussions in ushul fiqh. Ijtihad is an effort made by experts in Islamic law to explore laws that do not have clear arguments from sources of Islamic law. Those who perform Ijtihad are called Mujtahid. To achieve this goal, this article begins with a discussion of the meaning of Maqashid Shari'ah and its benefits, the meaning of Ijtihad and its urgency. The Maqashid impact in Ijtihad. The danger of an excessive Maqashid approach in Ijtihad without paying attention to the rules that have been set. The method used in writing this article is a literature review method by reviewing and referring directly to primary and secondary references in the study of Maqashid and Ijtihad. Keywords: Maqashid Syari’ah, Ijtihad, and Syari’ah.